Do Environmental Markets Improve on Open Access? Evidence from California Groundwater Rights - Ayres, Andrew B.; Meng, Kyle C.; Plantinga, Andrew J. (Journal of Political Economy, 2021)
Environmental markets are widely prescribed as an alternative to open access regimes for natural resources. We develop a model of dynamic groundwater extraction to demonstrate how a spatial regression discontinuity design that exploits a spatially incomplete market for groundwater rights recovers a lower bound on the market’s net benefit. We apply this estimator to a major aquifer in water-scarce southern California and find that a groundwater market generated substantial net benefits, as capitalized in land values. Heterogeneity analyses point to gains arising in part from rights trading, enabling more efficient water use across sectors. Additional findings suggest that the market increased groundwater levels.